2023
DOI: 10.1007/s00268-023-06970-1
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Digitalized Virtual Planning of Free Anterior Tibial Artery Perforator Flap for Repairing Soft Tissue Defects in Extremities

Abstract: Background Traditional research methods have limited the application of anterior tibial artery perforator flap due to incomplete knowledge of the perforator. This study aimed to investigate the feasibility of three‐dimensional digitalized virtual planning of free anterior tibial artery perforator flap for repairing soft tissue defects in extremities. Methods A total of 11 patients with soft tissue defects in extremities were included. The patient underwent computed tomography angiography (CTA) of bilateral low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Vascular supply at donor and recipient sites can vary significantly by individual [ 1 ]. In our clinical practice, we have found that computed-tomography angiography (CTA) not only accurately locates vascular structures but also provides high-throughput data on soft-tissue structures at the recipient and donor sites, which can aid in the selection of an optimal flap [ 2 , 3 ]. Therefore, we have developed a new surgical strategy, precise flap surgery based on CTA, to guide optimal flap selection and preparation.…”
Section: To the Editormentioning
confidence: 99%
“…Vascular supply at donor and recipient sites can vary significantly by individual [ 1 ]. In our clinical practice, we have found that computed-tomography angiography (CTA) not only accurately locates vascular structures but also provides high-throughput data on soft-tissue structures at the recipient and donor sites, which can aid in the selection of an optimal flap [ 2 , 3 ]. Therefore, we have developed a new surgical strategy, precise flap surgery based on CTA, to guide optimal flap selection and preparation.…”
Section: To the Editormentioning
confidence: 99%
“…The treatment of diabetic foot infections involves the surgical removal of the source of infection, isolation of causative pathogens, initiation of antibiotic treatment, optimization of host factors, and other adjunctive treatments [6][7][8][9][10]. Despite a better understanding of the pathophysiology and treatment of diabetic foot infection, one of the challenges encountered by the physicians treating these patients is wound healing [11][12][13][14][15][16][17]. Despite the recent advancements in wound dressing technologies and products, the wound healing process remains slow.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent advancements in wound dressing technologies and products, the wound healing process remains slow. Surgical interventions, such as skin grafting and flap coverage, can expedite wound coverage [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%